The Study of the Kangen Yogyakarta Market from the Viewpoint of a Traveler Experiencing the Culinary Festival - Suci Sandi Wachyuni; Kadek Wiweka; Mohammad Rizky Ferdinandsyah; Nenny Wahyuni (Journal of Tourism and Economic, 2023)
Culinary is intricately connected to the creation of processed foods and beverages that are characteristic of a certain region. In Indonesia, a diverse range of gastronomic delights with distinct flavors may be found from Sabang to Merauke. Nevertheless, the swift advancement of technology in the culinary domain has led to novel breakthroughs in the creation of food and drink items, which have the potential to alter the presence of traditional local cuisine. In order to prevent the marginalization of local cuisine, several strategies are implemented to promote it, one of which is organizing a festival. Every year, Yogyakarta has a Pasar Kangen Festival. This festival has the capacity to "revive" or "showcase" the presence of local cuisine and enhance the economic status of micro, small, and medium enterprises (MSMEs). This study employed a quantitative descriptive-analytic approach, utilizing Google Forms questionnaires to collect data from a sample size of 50 respondents. This study aims to assess the perception of individuals who have attended the Yogyakarta Pasar Kangen Festival regarding local food. The study population consisted of tourists who were visiting Yogyakarta, whereas the sample specifically included visitors who had visited the Pasar Kangen Festival. The findings of this survey suggest a prevailing public interest in visiting the Pasar Kangen as a whole. Moreover, the primary factors that attract visitors are the diverse culinary offerings and the distinctive local cuisine. Their primary incentive for visiting the Pasar Kangen is self-driven and external factors from the gratification they derive from the experience. The beauty and main draw of the Pasar Kangen Festival lies in its diverse and distinctive gastronomic offerings. The research aims to elucidate the theoretical implications by examining tourists' impression of festival events. The practical implication is to offer valuable information to the event manager and destination in order to enhance their focus on the diverse and distinctive food offerings at the festival, ultimately leading to increased tourist satisfaction.